Investigation of Social Appearance Anxiety Levels of Physical Education and Teaching, Coaching Education and Sports Management Department Students in Terms of Different Variables - İbrahim Kubilay Türkay (Journal of Educational Issues, 2024)
This research was carried out in order to determine the anxiety levels of the students of the Faculty of Sport Sciences, who are studying at Mehmet Akif Ersoy University in the province of Burdur, in the Republic of Turkey, according to their departments, due to their social appearance. The population of the research is Mehmet Akif Ersoy University, a higher education institution in Burdur, and the sample is a total of 201 university students, 57 female and 144 male, studying in the “Physical Education and Sports Teaching, Sports Management and Coaching Education” departments of the sports sciences faculty of this university has created. The “Social Physics Anxiety Inventory” scale, which was developed by Hart et al. (1989) and was adapted to Turkey by Mülazımoğlu, Ballı, and Aşçı (2006), consisting of 12 items and two sub-scales, was developed by Hart et al. (1989) in order to measure students’ anxiety levels towards their social appearance (Doğan, 2010; Mülazımoğlu-Ballı & Aşçı, 2004). Only the 7-item part, which is suitable for the characteristics of the Turkish people, was used. Appropriate SPSS program was used for the analysis of the data obtained in the research. In addition, before starting the research, the students filled out a “Voluntary Consent Form” to declare that they participated in the research voluntarily. “Pearson Correlation” test to examine the relationship between variables, the “Independent Samples” test to detect the effects of variables on each other, and the one-way analysis of variance test (One-Way ANOVA) to detect the difference between groups, and multiplexes to find between which groups this difference is “Bonferroni” test which is one of the comparison tests (Post Hoc) was applied. Significant differences were taken as p < 0.01 and p < 0.05. As a result of the research, it has been determined that there are positive and negative significant differences in the anxiety levels of 51 female and 144 male students studying at Burdur Mehmet Akif Ersoy University, Faculty of Sports Sciences, Physical Education and Sports Teaching, Sports Management and Coaching Education departments. Regarding the evaluation of these determinations, it can be said that female students are more sensitive than male students in terms of social appearance.